Analisis Dampak Jual Beli Online Dengan Sistem Cash On Delivery (COD) Terhadap Costumer Dan Kurir Dalam Kajian Ekonomi Islam di Kelurahan Sidorame - Ali Akbar Harahap; Sugianto Sugianto; Nurul Jannah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to identify and analyze the implementation of cash on delivery in buying and selling online at the Shopee market place. To find out and analyze the impact of buying and selling online with the cash on delivery (COD) system on customers and couriers in the perspective of Islamic Economics. The research design used was qualitative descriptive research. Data collection techniques in this study used interviews and documentation techniques. Data analysis techniques in this study used data reduction, data presentation and conclusion. The results of the study show that the mechanism or method of buying and selling online with the Cash On Delivery system that is carried out by cash on delivery at the Shopee Community of Sidorame Village is to create a Shopee account first, then promote goods from suppliers or online shops that have been selected from the Shopee application by uploading photos. - interesting photos to social media, when there is an order then start searching/selecting and buying goods on the Shopee application, after finishing selecting then fill in the complete buyer's address, then select the payment method to be used, then check the words "send as cash on delivery. An Islamic economic study of buying and selling online with the Cash On Delivery system carried out by cash on delivery at the Shopee Community of the Sidorame Village shows that this buying and selling is not in line with the concept of bai' assalam, especially parallel greetings & basic principles/values ​​of business ethics in the Islamic economy where there are elements the lack of clarity regarding the goods sold by Shopee cash on delivery, because cash on delivery does not own, know or see the original form of the goods in real terms. Then there is no element of honesty (openness) by the cash on delivery party to the buyer regarding the system used.